Speaker-specific processing of anomalous utterances. - Brehm, Laurel; Jackson, Carrie N.; Miller, Karen L. (Quarterly Journal of Experimental Psychology, 2019)
Existing work shows that readers often interpret grammatical errors (e.g., The key to the cabinets *were shiny) and sentence-level blends ("without-blend": Claudia left without her headphones *off) in a non-literal fashion, inferring that a more frequent or more canonical utterance was intended instead. This work examines how interlocutor identity affects the processing and interpretation of anomalous sentences. We presented anomalies in the context of "emails" attributed to various writers in a self-paced reading paradigm and used comprehension questions to probe how sentence interpretation changed based upon properties of the item and properties of the "speaker." Experiment 1 compared standardised American English speakers to L2 English speakers; Experiment 2 compared the same standardised English speakers to speakers of a non-Standardised American English dialect. Agreement errors and without-blends both led to more non-literal responses than comparable canonical items. For agreement errors, more non-literal interpretations also occurred when sentences were attributed to speakers of Standardised American English than either non-Standardised group. These data suggest that understanding sentences relies on expectations and heuristics about which utterances are likely. These are based upon experience with language, with speaker-specific differences, and upon more general cognitive biases.